Optimizing the Readiness of School-Age Children to Face the New Normal Era in Suka Makmur Village, Deli Tua District - Daulay, Wardiyah; Nasution, Mahnum Lailan; Sri Eka Wahyuni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
A school age child is someone who is in the age range of 6-12 years and has met the requirements to attend school because of the intellectual development of the child. School-age children usually receive learning at school using the offline method, but during this pandemic this turned into online at home. Currently the government has started implementing the new normal, including several schools that are in the green zone allowed to modify the combined learning method between online and offline. For this reason, it is very necessary to provide education about what behavior should be done by school children after the government later allows offline schools. Efforts that can be made to optimize children's readiness in the new normal are by assisting children to be able to behave with new habits, namely wearing masks, washing hands, using personal tools from home and avoiding crowds. The community service carried out aims to optimize the readiness of school-age children by providing information support about the behavior that children should do during the Covid 19 pandemic. The method is carried out by providing education through leaflets about the adaptation of new normal habits with online and offline media. The results of community service are the results of increasing children's knowledge about habits that must be done in the face of the new normal. The output of the service is in the form of videos, leaflets, data on children's knowledge and mask products with children's characters.